A clinical utility study of exome sequencing versus conventional genetic testing in pediatric neurology - Vissers, Lisenka E.L.M.; van Nimwegen, Kirsten J.M.; Schieving, Jolanda H.; Kamsteeg, Erik-Jan; Kleefstra, Tjitske; Yntema, Helger G.; Pfundt, Rolph; van der Wilt, Gert Jan; Krabbenborg, Lotte; Brunner, Han G.; van der Burg, Simone; Grutters, Janneke; et al. (Genetics in medicine, 2017)
Purpose: Implementation of novel genetic diagnostic tests is generally driven by technological advances because they promise shorter turnaround times and/or higher diagnostic yields. Other aspects, including impact on clinical management or cost-effectiveness, are often not assessed in detail prior to implementation. Methods: We studied the clinical utility of whole-exome sequencing (WES) in complex pediatric neurology in terms of diagnostic yield and costs. We analyzed 150 patients (and their parents) presenting with complex neurological disorders of suspected genetic origin. In a parallel study, all patients received both the standard diagnostic workup (e.g., cerebral imaging, muscle biopsies or lumbar punctures, and sequential gene-by-gene–based testing) and WES simultaneously. Results: Our unique study design allowed direct comparison of diagnostic yield of both trajectories and provided insight into the economic implications of implementing WES in this diagnostic trajectory. We showed that WES identified significantly more conclusive diagnoses (29.3%) than the standard care pathway (7.3%) without incurring higher costs. Exploratory analysis of WES as a first-tier diagnostic test indicates that WES may even be cost-saving, depending on the extent of other tests being omitted. Conclusion: Our data support such a use of WES in pediatric neurology for disorders of presumed genetic origin. Genet Med advance online publication 23 March 2017